The Characteristics of Primary Open Angle Glaucoma Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Felia Noor Haliza Putri; Fidalia; Puspa Zuleika; Prima Maya Sari; Ramzi Amin (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2022)
Introduction. Many people in Indonesia are unfamiliar with glaucoma, even though it causes blindness. This fact is because the damage process of glaucoma occurs slowly. If glaucoma is not treated immediately, it can cause irreversible vision loss and blindness. This study aims to present the characteristics of primary open-angle glaucoma patients at Dr. Mohammad Hoesin General Hospital Palembang, Indonesia. Methods. This study is a descriptive observational study. A total of 33 subjects participated in this study. Data analysis was carried out with SPSS for Windows. Results. Most participants were men aged 40-69 years old with a history of high school education. Most patients had clinical symptoms with a mild cup-to-disc ratio with early degrees of visual field defects and intraocular pressure less than 21 mmHg with therapy. Most patients had no history of hypertension, no history of diabetes mellitus and no family history of similar disorders. Most patients have refractive disorders and received medical therapy. Conclusion. The characteristics of primary open-angle glaucoma patients at Dr. Mohammad Hoesin General Hospital have a clinical form of a mild cup-to-disc ratio, refractive disorders and receive medical therapy to control increased intraocular pressure.